Pediatric skills for occupational therapy assistants - Jean W. Solomon; Jane Clifford O'Brien (St. Louis Missouri : Elsevier, 2021)
Learn to provide effective therapy for children and adolescents! Pediatric Skills for Occupational Therapy Assistants, 5th Edition covers the entire scope of pediatric OT practice, from normal childhood development to pediatric disorders and treatment planning. Case studies and helpful tips reinforce your understanding and make it easier to apply OT principles to the clinical setting. This edition is thoroughly updated with online videos and new coverage of community systems, physical agent modalities, childhood obesity, Model of Human Occupation assessments, and Kinesio Taping®. Written by noted OTA educators Jean Solomon and Jane O'Brien, this resource is both a comprehensive textbook and a practical clinical reference!
Keywords: Adolescent Development; Occupational Therapy methods; Child Development